From Symptoms to Survival: Tracking COVID-19 Patient Outcomes in an Outpatient Clinic: COVID-19 Outpatient Outcomes - Sadeghi, Somayeh; Hashemi, Huriyeh; Tavakoli, Fereshteh; Kazemi-Galougahi, Mohammad Hassan; Iraj, Bijan; Tarrahi, Mohammad Javad; Khaleghi, Mohammad Hossein; Abdeyazdan, Neda; Saghaei, Mozhdeh (Medicinski časopis, 2025)
Background and Aim: The Coronavirus Disease 2019 (COVID-19) pandemic has significantly impacted public health, requiring a deeper understanding of its transmission, pathogenesis, and effective treatment strategies. This study aims to investigate the clinical outcomes of COVID-19 patients treated at an outpatient respiratory clinic, focusing on the impact of comorbidities on mortality rates. Methods: We conducted a retrospective cohort study at Al-Zahra Hospital’s outpatient respiratory clinic, involving 524 patients diagnosed with COVID-19 through PCR tests or CT scans. The study focused on evaluating changes in clinical status, laboratory parameters, vital signs, and 28-day mortality rates after treatment. Results: An analysis of 524 COVID-19-confirmed participants demonstrated statistically significant correlations between mortality, history of cardiovascular disease, and diabetes (p < 0.05). However, the associations between mortality and diverse factors, such as gender, psychiatric disorders, neurological diseases, renal diseases, hypertension, and the number of vaccinations, were not statistically significant (p > 0.05). Conclusion: The study revealed increased COVID-19-related mortality rates in individuals particularly with cardiovascular disease and diabetes. No substantial correlation was observed between mortality and age, gender, other illnesses, and laboratory data.